1984
DOI: 10.1002/jnr.490120225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GM1 ganglioside treatment on postlesion responses of cholinergic enzymes in rat hippocampus after various partial deafferentations

Abstract: The effect of intramuscular administration of monosialoganglioside (GM1) on postlesion responses of choline acetyltransferase and acetylcholinesterase activity in partially deafferented rat hippocampus was studied at various survival times. Lesions partially destroying the medioventral, septal area, or lesions performed in supracallosal stria including corpus callosum and cingulum evoked cholinergic denervation of the hippocampus, while those made in entorhinal cortex resulted in partial glutamatergic deaffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Experimental evidence has shown that gangliosides facilitate cholinergic reinnervation after lesions of the septal nuclei or of the nucleus basalis, or after transection of the fimbria-fornix [34][35][36][37][38]. In addition, GM1 exhibited neuroprotection and promoted reinnervation of cholinergic neurons after cortical infarction, which produces well-defined anatomical and biochemical deficits of the nucleus basalis in rats as well as nonhuman primates [39][40][41][42]. Remarkably, GM1 can also promote morphological and functional recovery in normal aged animals.…”
Section: Chronic Degenerationmentioning
confidence: 85%
“…Experimental evidence has shown that gangliosides facilitate cholinergic reinnervation after lesions of the septal nuclei or of the nucleus basalis, or after transection of the fimbria-fornix [34][35][36][37][38]. In addition, GM1 exhibited neuroprotection and promoted reinnervation of cholinergic neurons after cortical infarction, which produces well-defined anatomical and biochemical deficits of the nucleus basalis in rats as well as nonhuman primates [39][40][41][42]. Remarkably, GM1 can also promote morphological and functional recovery in normal aged animals.…”
Section: Chronic Degenerationmentioning
confidence: 85%
“…In this context, although the exact mechanism by which GM1 ganglioside modifies cholinergic function in young and old rats is still under investigation, there is a considerable number of evidence suggesting that GM1 effects could be cholinergic in nature. It has been verified, for example, that IM administration of gangliosides potentiated post-lesion response of choline acetyltransferase and acetylcholinesterase in rat hippocampus after medioventral and septal lesions (Wojcik et al 1982;Oderfeld-Nowak et al 1984). In addition, GM1 treatment was able to increase cortical acetylcholine release in vivo in rats with unilateral decortication (Maysinger et al 1988(Maysinger et al , 1990.…”
Section: Discussionmentioning
confidence: 97%
“…GM1 ganglioside is a normal constituent of nerve cell membranes, is known to modulate a number of cell surface and receptor activities and plays important roles in neuronal differentiation and development [6], protein phosphorylation [7], and synaptic function [8]. Treatment with GM1 following a number of different types of central nervous system lesions in experimental animals [9][10][11][12][13][14] has resulted in significant biochemical and behavioral recovery and pretreatment with GM1 inhibits damage resulting from a variety of neurotoxic exposures [15][16][17]. GM1 administration has been effective in ameliorating neurochemical and behavioral alterations in murine and non-human primate models of PD [13,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%